HUBUNGAN AKTIVITAS ENZIM DAN KONSENTRASI SUBSTRAT PADA POLA DETEKSI SECARA HPLC HASIL TRANSGLIKOSILASI NARINGENIN OLEH ENZIM SELULASE Penicillium sp. LBKURCC27 - Puspita Sari; Titania Tjandrawati Nugroho; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Transglycosylation of naringenin was carried out by concentrated cellulase enzyme of Penicillium sp. LBKURCC27. Enzymatic transglycosylation of naringenin was successfully carried out by cellulase from Penicillium sp. LBKURCC27, however the reproducibility of the reaction is low, making detection by reverse phase HPLC (High Performance Liquid Chromatography) difficult when the enzyme activity decreases. It is believe that the flavonoid concentration used in the transglycosylation naringenin by cellulase Penicillium sp. LBKURCC27 influences the detection pattern of transglycosylation product of HPLC. The reaction was carried out for 30 hours at 40°C with acetate buffer 0.05 M pH 5.5 and 170 rpm shaking. Carboxymethyl Cellulose (CMC) was used as glycosyl donor. Results of HPLC analysis showed that cellulase Penicillium sp. LBKURCC27 with an activity of (0.670±0.023 U/mL) were not able to convert naringenin to a detectable glycosylated product when the initial substrate concentration was 6 mg/mL. In the 0.6 mg/mL of naringenin concentration, the glycosylation product was formed with 100% of percent convertion.